Population‐based study of multisystem inflammatory syndrome associated with COVID‐19 found that 36% of children had persistent symptoms. (1st December 2021) - Kahn, Robin; Berg, Stefan; Berntson, Lillemor; Berthold, Elisabet; Brodin, Petter; Bäckström, Fredrik; Compagno, Michele; Fasth, Anders; Lingman Framme, Jenny; Horne, AnnaCarin; Hätting, Josefin; Król, Petra; et al.
Abstract: Aim: Our aim was to describe the outcomes of multisystem inflammatory syndrome in children (MIS‐C) associated with COVID‐19. Methods: This national, population‐based, longitudinal, multicentre study used Swedish data that were prospectively collected between 1 December 2020 and 31 May 2021. All patients met the World Health Organization criteria for MIS‐C. The outcomes 2 and 8 weeks after diagnosis are presented, and follow‐up protocols are suggested. Results: We identified 152 cases, and 133 (87%) participated. When followed up 2 weeks after MIS‐C was diagnosed, 43% of the 119 patients had abnormal results, including complete blood cell counts, platelet counts, albumin levels, electrocardiograms and echocardiograms. After 8 weeks, 36% of 89 had an abnormal patient history, but clinical findings were uncommon. Echocardiogram results were abnormal in 5% of 67, and the most common complaint was fatigue. Older children and those who received intensive care were more likely to report symptoms and have abnormal cardiac results. Conclusion: More than a third (36%) of the patients had persistent symptoms 8 weeks after MIS‐C, and 5% had abnormal echocardiograms. Older age and higher levels of initial care appeared to be risk factors. Structured follow‐up visits are important after MIS‐C.